Adsorption Mechanism of Chitosan Biopolymer on Sandstone Media: Salinity and Concentration Effects - Awan, Herlina Imeli; Rahman, Muhammad Rizqie Fathan; Ulfah, Baiq Maulinda; Ma arif, Muhammad Syaiful Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the adsorption mechanism of shrimp chitosan on 40-mesh silica sand under varying salinity and concentration conditions as a basis for evaluating its potential as an environmentally friendly polymer for Green Enhanced Oil Recovery (EOR) applications. Chitosan was prepared at concentrations of 5000, 10000, and 15000 mg/L, with NaCl salinities of 10000 and 20000 mg/L. Batch adsorption experiments were conducted, and adsorption behavior was evaluated using Henry, Freundlich, Langmuir, and Harkins–Jura isotherm models. The results show that the Freundlich and Langmuir models provide a better representation of chitosan adsorption behavior than the Henry and Harkins–Jura models. Chitosan adsorption exhibits greater stability at higher salinity and tends to follow a monolayer adsorption mechanism on heterogeneous surfaces. These findings highlight the importance of a multi-isotherm approach in understanding biopolymer adsorption behavior and indicate that shrimp chitosan has potential as an environmentally friendly polymer for chemical injection in sandstone reservoirs.